A Kunitz-type inhibitor from tick salivary glands: A promising novel antitumor drug candidate - Lobba, Aline R. M.; Alvarez-Flores, Miryam Paola; Fessel, Melissa Regina; Buri, Marcus Vinicius; Oliveira, Douglas S.; Gomes, Renata N.; Cunegundes, Priscila S.; DeOcesano-Pereira, Carlos; Cinel, Victor D.; Chudzinski-Tavassi, Ana M. (Frontiers in Molecular Biosciences, 2022)
Salivary glands are vital structures responsible for successful tick feeding. The saliva of ticks contains numerous active molecules that participate in several physiological processes. A Kunitz-type factor Xa (FXa) inhibitor, similar to the tissue factor pathway inhibitor (TFPI) precursor, was identified in the salivary gland transcriptome of Amblyomma sculptum ticks. The recombinant mature form of this Kunitz-type inhibitor, named Amblyomin-X, displayed anticoagulant, antiangiogenic, and antitumor properties. Amblyomin-X is a protein that inhibits FXa in the blood coagulation cascade and acts via non-hemostatic mechanisms, such as proteasome inhibition. Amblyomin-X selectively induces apoptosis in cancer cells and promotes tumor regression through these mechanisms. Notably, the cytotoxicity of Amblyomin-X seems to be restricted to tumor cells and does not affect non-tumorigenic cells, tissues, and organs, making this recombinant protein an attractive molecule for anticancer therapy. The cytotoxic activity of Amblyomin-X on tumor cells has led to vast exploration into this protein. Here, we summarize the function, action mechanisms, structural features, pharmacokinetics, and biodistribution of this tick Kunitz-type inhibitor recombinant protein as a promising novel antitumor drug candidate.